Impact of early-life events on the susceptibility to Clostridium difficile colonisation and infection in the offspring of the pig - Grześkowiak, Łukasz M. (Gut Microbes, 2018)
Clostridium difficile has been documented as a major cause of uncontrolled outbreaks of enteritis in neonatal pigs and antibiotic-associated infections in clinical settings. It belongs to the natural cohort of early colonisers of the gastrointestinal tract of pigs and can be detected in faeces up to two weeks post-partum. In older pigs, it often remains under the detection limit. Most neonatal pigs show no clinical signs of disease although C. difficile and its toxins can be detected at high levels in faeces. Increased mortality rates associated with C. difficile on pig farms are, so far, considered “spontaneous” and the predisposing factors are mostly not defined. The infection caused by C. difficile is multifactorial and it is likely that the repertoire of maternal factors, host physiology, the individually developing gut microbiota, co-infections and environmental stress define the conditions for disease development. In this addendum to our recently published work on CDI in neonatal piglets, we discuss the “early-life events” that influence C. difficile spread and infection in neonatal piglets.